2022
DOI: 10.29333/ejmste/12732
|View full text |Cite
|
Sign up to set email alerts
|

The development and validation of environmental literacy instrument based on spirituality for prospective science teachers

Abstract: The spiritual (S) aspect needs to be integrated with the environmental literacy instrument (ELI) so that it becomes ELIS. This study was designed to develop and validate an instrument for prospective science teacher in the form of environmental literacy instrument based on literacy (ELIS). The instrument was developed based on previous research findings and focus group discussions involving eleven experts. The factors and internal consistency were examined by involving 634 students/prospective science teachers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
1
7
0
2
Order By: Relevance
“…This research also revealed interesting results regarding the relationship between teachers' EL levels and their educational areas, accompanying learning area engagement, and environmental education training in general (An et al, 2022;Cincera et al, 2021). In this regard, an Environmental Literacy Instrument based on Spirituality (ELIS) has been developed (Husamah et al, 2022), in the Indonesian context. Therefore, this instrument has potency to be used.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…This research also revealed interesting results regarding the relationship between teachers' EL levels and their educational areas, accompanying learning area engagement, and environmental education training in general (An et al, 2022;Cincera et al, 2021). In this regard, an Environmental Literacy Instrument based on Spirituality (ELIS) has been developed (Husamah et al, 2022), in the Indonesian context. Therefore, this instrument has potency to be used.…”
Section: Introductionmentioning
confidence: 92%
“…The analysis results of internal consistency reveal that the value of CR is 0.73-0.94 and Cronbach's alpha is 0.72-0.94 or ≥0.7 (meets the criteria). The AVE value of 0.52-0.65 or ≥0.5 (meets the criteria) (Husamah et al, 2022). The target respondents were very large and broad, covering all of Indonesia, so based on these conditions, the survey process was carried out online.…”
Section: Data Collection Instruments and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Seiring perubahan masyarakat, keterampilan yang dibutuhkan warga untuk merundingkan kompleksitas kehidupan juga berubah (Kryukova et al, 2022). Pada awal 1900-an, seseorang yang telah memperoleh keterampilan membaca, menulis, dan juga berhitung sederhana dianggap melek huruf (Husamah et al, 2022). Beberapa tahun belakangan ini sistem pendidikan mengharapkan semua siswa untuk belajar membaca dan berfikir secara kritis (Fan & Wang, 2022), menulis dengan persuasif, berpikir dan bernalar secara logis (Dorner & Ableitinger, 2022;Mafarja et al, 2022), dan memecahkan masalah kompleks dalam matematika dan sains (He & Qi, 2022) Di Indonesia saat ini telah mengalami perubahan yang sangat cepat dalam perkembangan teknologi, dan sebagian besar pekerjaan harus beroperasi secara global untuk bertahan dalam persaingan yang ada di dunia saat ini.…”
Section: Pendahuluanunclassified
“…Domain yang kelima norma dan nilai spiritual (norms and spiritual values) yang memiliki tiga aspek yang saling berhubungan yaitu aspek mampu menerima agama sebagai cara hidup, mampu mengaitkan nilai spiritual dengan pengetahuan, dan wujud syukur mempelajari sains (Husamah et al, 2022). Domain keenam yaitu nilai keberagaman (multicultural values), domain ini memiliki empat aspek yang saling berhubungan yaitu 1) aspek kesadaran bahwa nilai keberagaman dapat mempengaruhi cara bertindak, 2) menghargai, menerima persamaan dan perbedaan keyakinan, penampilan, dan gaya hidup, 3) peduli dan peka terhadap informasi, dan 4) mengerti pentingnya norma budaya, lingkungan dan mampu untuk berinteraksi di dalamnya.…”
Section: Hasil Dan Pembahasanunclassified